Problems of Urdu speakers in learning English consonants - Sayyid, Muhammad Abdul-Wahid. ([Quezon City s.n.], 1964)
This is an identification of the problems encountered by Urdu speakers in learning the English consonant sounds. This is done by comparing the phonemes, the allophones, and the distribution of sounds in Urdu and English. The phonemic symbols used in this study were those of the International Phonemic Association (IPA) with some modifications to suit the typing process.
Thesis (M.Ed.)--University of the Philippines
Keywords: Urdu language; English language in Pakistan